The electrochemistry of ferrocene in non-aqueous solvents - Zara, Alfredo J.; Machado, Sérgio S.; Bulhões, Luis Otávio S.; Benedetti, Assis Vicente [UNESP]; Rabockai, Tibor (Elsevier, 1987)
the electrochemical oxidation of ferrocene on Pt in dimethylformamide, ethanol, propylene carbonate and their aqueous solutions was studied at 25°C. The concentration of the supporting electrolyte, NaClO4, was varied from 0.1 to 0.5 M. The results show that the electrode process may be described as a quasi-reversible one-electron charge transfer, followed by slow decomposition of the oxidized species. © 1987.